Características clínico – epidemiológicas de pacientes hospitalizados fallecidos por COVID 19. Hospital Belén de Trujillo, 2020 - Navarro Rosell, Yovana Rosmery (2022)
The COVID-19 pandemic has represented an instability in the health system worldwide and our country has not been the exception, even with all the plans implemented for the surveillance of the pandemic, it is seen that these have been deficient in the context of destruction of the health system. Currently in our country an increase in mortality figures is being visualized, for this reason we set ourselves the following objective, to determine what are the clinical-epidemiological characteristics of hospitalized patients who died of COVID 19 at the Hospital Belén de Trujillo from May 1 to on December 31, 2020. For which we will work with the medical records of each patient who was hospitalized for COVID 19, in the aforementioned period and who have died in said hospital. The procedure will be recorded in a data collection form for each patient. The anonymity and confidentiality of the information will be guaranteed. To review the information, tables will be prepared, which will be frequency, single and double entry, each with its absolute and relative values, to which descriptive statistics will be added. This study seeks to deepen what factors are associated with the mortality of patients diagnosed with COVID 19.